2014
DOI: 10.1038/nn.3886
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pain in vitro using nociceptor neurons reprogrammed from fibroblasts

Abstract: Reprogramming somatic cells from one cell fate to another can generate specific neurons suitable for disease modeling. To maximize the utility of patient-derived neurons, they must model not only disease-relevant cell classes but also the diversity of neuronal subtypes found in vivo and the pathophysiological changes that underlie specific clinical diseases. Here, we identify five transcription factors that reprogram mouse and human fibroblasts into noxious stimulus-detecting (nociceptor) neurons that recapitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
189
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(203 citation statements)
references
References 59 publications
(84 reference statements)
8
189
0
1
Order By: Relevance
“…Indeed, this approach has been used for inducing many other neuronal subtypes lost in traumatic injury or neurodegenerative diseases, and generation of which in vitro could be potentially useful for cellbased therapies as well as for disease modelling (Blanchard et al, 2015;Caiazzo et al, 2011;Gascón et al, 2016;Rouaux and Arlotta, 2013;Son et al, 2011;Victor et al, 2014;Wainger et al, 2015). Especially for the latter, direct reprogramming has the advantage of maintaining the age of the starter cell (Mertens et al, 2015), in contrast to the re-setting that occurs when generating induced pluripotent stem cells (Lapasset et al, 2011).…”
Section: Neuronal Subtype Specification: From Dopaminergic Neurons Tomentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, this approach has been used for inducing many other neuronal subtypes lost in traumatic injury or neurodegenerative diseases, and generation of which in vitro could be potentially useful for cellbased therapies as well as for disease modelling (Blanchard et al, 2015;Caiazzo et al, 2011;Gascón et al, 2016;Rouaux and Arlotta, 2013;Son et al, 2011;Victor et al, 2014;Wainger et al, 2015). Especially for the latter, direct reprogramming has the advantage of maintaining the age of the starter cell (Mertens et al, 2015), in contrast to the re-setting that occurs when generating induced pluripotent stem cells (Lapasset et al, 2011).…”
Section: Neuronal Subtype Specification: From Dopaminergic Neurons Tomentioning
confidence: 99%
“…From a developmental perspective, these neurons differentiate from neural crest cells (Pavan and Raible, 2012), and hence a promising approach for generating them has been to reprogramme human fibroblasts into neural crest cells, which can then be further differentiated into peripheral neurons . However, direct neuronal reprogramming has proven to be more successful in obtaining specific subtypes of peripheral neurons than the neural crest cell route (Blanchard et al, 2015;Wainger et al, 2015). As peripheral sensory neurons are different to those of the central nervous system, an important question is how similar or different the molecular requirements are for inducing these cells.…”
Section: Peripheral Sensory Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, access to authentic human peripheral sensory neurons represents an important scientific goal with potentially large clinical implications. Two groups recently reported exciting findings that suggest that mouse and human fibroblasts can be converted to iN cells with even such a high degree of subspecialization as the three main classes of peripheral sensory neurons, including nociceptive neurons that would be highly relevant for pain research [59,60]. The Baldwin group found that just two transcription factors, either Ngn1 or Ngn2, in combination with Brn3a, a critical lineage determination factor for peripheral neurons, was sufficient to convert both mouse primary and human iPS cell-derived fibroblasts to iN cells with peripheral identity representing the three major classes of sensory neurons: nociceptive, mechanosensitive and proprioceptive, which express the key specific markers TrkA, B and C, respectively [59].…”
Section: (D) Generation Of Induced Peripheral Sensory Neuronsmentioning
confidence: 99%